1983
DOI: 10.1002/1097-0142(19830915)52:6<967::aid-cncr2820520605>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Remission of acute myelogenous leukemia in elderly patients with prior refractory dysmyelopoietic anemia

Abstract: Refractory dysmyelopoietic anemia (RDA) is a myeloproliferative disorder usually of elderly patients which often evolves into acute myelogenous leukemia (AML). AML in such patients is usually considered untreatable with standard aggressive chemotherapy in part because these patients are often elderly, but primarily because of the concern that the bone marrow of these patients no longer has a residual stem cell to repopulate the bone marrow following chemotherapy‐induced aplasia. The authors treated three patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Data on the response to these therapies remain scarce and conflicting. A favourable outcome after intensive chemotherapy has been reported (Hussein et al, 1982;Murray et al, 1983;Yunis and Brunning, 1986), but other workers have observed poor responses (Mertelsmann et al, 1980;Tricot and Boogaerts, 1986). Low dose Ara-C has been disappointing in this indication (Tricot et al, 1984;Winter er al., 1985;Martiat et ai., 1986).…”
Section: Introductionmentioning
confidence: 92%
“…Data on the response to these therapies remain scarce and conflicting. A favourable outcome after intensive chemotherapy has been reported (Hussein et al, 1982;Murray et al, 1983;Yunis and Brunning, 1986), but other workers have observed poor responses (Mertelsmann et al, 1980;Tricot and Boogaerts, 1986). Low dose Ara-C has been disappointing in this indication (Tricot et al, 1984;Winter er al., 1985;Martiat et ai., 1986).…”
Section: Introductionmentioning
confidence: 92%
“…Several treatment modalities with encouraging results have been proposed for myelodysplastic syndromes and subsequent acute non-lymphocytic leukaemias including retinoic acid ( 5 , 12), low dose cytosine arabinoside (13,14) and conventional doses of chemotherapy (15). Whether or not the t(2;ll) (p21;q23) will turn out to identify a subgroup of patients within the spectrum of myelodysplastic disorders and ANLL with respect to morphology of the malignant cell, clinical features, response to therapy, or prognosis, is not yet clear.…”
Section: Clinical Outcome Response To Treatmentmentioning
confidence: 99%